2021
DOI: 10.20944/preprints202104.0352.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Improved SCS-CN Model Incorporating Storm Duration and Rainfall-based Initial Abstraction for Runoff Estimation

Abstract: The need of incorporating storm intensity or duration in Soil Conservation Service Curve Number (SCS-CN) methodology for improved direct surface runoff estimation for a watershed has been highlighted by many engineers and hydrologists since long and despite this fact, it is still poorly explored. Therefore, this study aims to present storm duration-based improved SCS-CN models for estimating more accurate direct surface runoff from rainfall events. The accuracy and consistency of improved models are tested on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 60 publications
(71 reference statements)
0
1
0
Order By: Relevance
“…According to Adornado and Yoshida (2010), Moretti and Montanari (2008), Soulis and Valiantzas (2012), and Mishra and Singh (2004), this method has become an inseparable part of many simulation models. Furthermore, the SCS-CN method can be applied to various landscape structures, soils, and climate conditions (Warner et al 2010;Vojtek and Vojteková 2016;Singh et al, 2015;Tedela et al, 2012;Mishra et al, 2012;Verma et al, 2021). These researchers have also indicated that the SCS-CN method can be effectively used for small and large river basins with heterogeneous land uses.…”
Section: Estimation Of a Design Flood Using The Scs-cn Methodologymentioning
confidence: 99%
“…According to Adornado and Yoshida (2010), Moretti and Montanari (2008), Soulis and Valiantzas (2012), and Mishra and Singh (2004), this method has become an inseparable part of many simulation models. Furthermore, the SCS-CN method can be applied to various landscape structures, soils, and climate conditions (Warner et al 2010;Vojtek and Vojteková 2016;Singh et al, 2015;Tedela et al, 2012;Mishra et al, 2012;Verma et al, 2021). These researchers have also indicated that the SCS-CN method can be effectively used for small and large river basins with heterogeneous land uses.…”
Section: Estimation Of a Design Flood Using The Scs-cn Methodologymentioning
confidence: 99%